Józef Darski (1942–2016) and his contribution to the German linguistics and grammar - Taborek, Janusz (Lingua Posnaniensis, 2016)
The linguist and grammarian, Józef Darski (born 30th August 1941) died on 18th March 2016 in Poznan. This contribution presents his life and innovative and original work. His outstanding achievement was a holistic, original, generic and empirical-based model of linguistic analysis, concerning all of its levels. Based on his model, Darski proposed original ways of presenting stems and exponents, a system of word classes, regular and irregular verbs, as well as noun and adjective declension. Józef Darski was a respected and esteemed teacher and a master for many Polish Germanists as well as a successful university administrator serving as dean of his faculty for several years. His death was a loss for German studies in Poland.